Introduction to company law - Davies, P. L. (Paul Lyndon) (Oxford : Oxford University Press, 2020)
Since the financial crisis of 2007 to 2009 the role of the company in society, especially the role of publicly traded companies, has acquired a political salience that was largely absent in the decades before the crisis. This concern has been reflected in both enhanced reporting requirements and in the latest version of the Corporate Governance and Stewardship Codes applicable to the largest companies. This books analyses these developments in full, as well as the more fundamental proposals for reform of corporate law that have been advanced outside official circles. The book also examines the functions of the five core features of company law-separate legal personality, limited liability, centralised management, shareholder control, and transferability of shares.
Previous edition issued in print: 2010.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 31, 2020).
Keywords: Corporation law -- Great Britain